Effect of doped fiber length on the stretch pulses of a mode-locked erbium-doped fiber laser - Tan, S.J.; Ismail, M.A.; Shahabuddin, N.S.; Ahmad, Harith; Arof, Hamzah; Harun, Sulaiman Wadi (IOP Publishing, 2012)
A passively self!starting mode!locked fiber ring laser is demonstrated using a highly concentrated Erbium doped fiber (EDF) with a saturable absorber. The effect of EDF length on the performance of the laser is investigated. Stable stretched pulses are obtained at wavelength region of 1560nm with a repetition rate ranging from 10.1 to 12.1 MHz and a pulse width stretching from 0.52 to 0.75 ps as the EDF length is reduced from 4.5 to 1.5 m. The repetition rate goes higher as the cavity length decreases when a shorter EDF is used but the pulse width reduces as the EDF length increases since the total group velocity dispersion (GVD) in the cavity is close to zero.